Open access institutional repositories in universities in East Africa - Kakai, Miriam; Musoke, Maria G.N.; Okello-Obura, Constant (Information and Learning Science, 2018)
Purpose – Given that repositories were proposed as one of the routes to open access (OA), this study sought to establish the achievements universities in East Africa had attained in initiating institutional repositories (IRs), the challenges in providingOA and strategies for the way forward. Design/methodology/approach – Data were collected through literature searches, using the internet, journal databases and university websites in Kenya, Tanzania and Uganda for information about OA and IRs in East Africa. Some of the findings were based on the author’s PhD “The management and accessibility of OA IRs in selected universities in East Africa”, which used face-to-face interviews with six librarians and selfadministered questionnaires responded to by 183 researchers at Kenyatta University, Muhimbili University of Health and Allied Sciences and Makerere University. Findings – Universities in East Africa were still in the intermediate stages of embracing OA, and only 40 libraries out of 145 universities had implemented IRs. However, most of the repositories had less than 1,000 items, with this challenge attributed to the absence of institutional and government/funder mandates that affected the collection/provision of OA, in addition to the lack of awareness of IRs among researchers. Originality/value – The value in this research was establishing the extent of IR initiatives in universities in East Africa and their contribution to OA, which is regarded as more visible and accessible to scholars and government personnel who could leverage the information for further development in the region
Keywords: Open access; Kenya; East Africa; Universities